Clinical Practice: Vocal nodules in dysphonic children - Garcia Martins, Regina Helena [UNESP]; Branco, Anete [UNESP]; Mendes Tavares, Elaine Lara [UNESP]; Joia Gramuglia, Andrea Cristina [UNESP] (Springer, 2013)
Common among children, vocal symptoms are a cause of concern for parents who seek elucidation of their diagnosis and treatment. Vocal nodules are the major cause of dysphonias in children and are related to vocal abuse. We conducted a literature review considering clinical, physiopathological, epidemiological, and histological aspects of vocal nodules, as well as diagnostic methods, highlighting the main studies addressing this issue. The controversial points of treatments were also discussed.
Keywords: Vocal nodules; Children; Voice disorders; Dysphonia